Base‐Mediated Generation of Ketenimines from Ynamides: [3+2] Annulation with Azaallyl Anions. Issue 11 (12th April 2021) - D'Hollander, Agathe C. A.; Romero, Eugénie; Vijayakumar, Kamsana; Le Houérou, Camille; Retailleau, Pascal; Dodd, Robert H.; Iorga, Bogdan I.; Cariou, Kevin
Abstract: Under basic conditions and heat, ynamides can serve as precursors to ketenimines, whose synthetic potential is often hampered by their difficulty of access. Herein, we report that they can undergo a [3+2] cycloaddition with 2‐azaallyl anions, obtained from benzylimines under the same reaction conditions. This reaction between two highly reactive intermediates, both generated in situ from bench stable starting materials, gives access to various nitrogen‐rich heterocycles. The reaction usually proceeds with excellent diastereoselectivity, in favor of the cis adduct. Deuteration experiments and DFT calculations helped rationalize the regio‐ and stereoselectivity of the process as well as the formation of side products. Abstract :